Growth of human vertebral column and its parts during extrauterine - Zaborowski, Zbigniew (Anthropological Review, 1977)
On X-ray pictures of 200 vertebral columns of subjects in the age 0-26 years measurements of length of presacral parts together with medial height of vertebral bodies and intervertebral discs were taken. For the age groups 0-4 weeks, 1 year, 3, 7, 11-13, 16-18 and 22-26 years mean values and variability of measurements were computed. Absolute values of dimensions are higher in males. Variability increases with age and is the highest in the lumbar part. During ontogeny there is a tendency toward shortening of cervical part and lenghtening of the lumbar one, Relative length of the parts of the vertebral column changes with age as well as the share of cartilagincous and osseous components in their total length. The vertebral column shows a growth dynamics slightly different from that described in the literature. The backbone grows most intensively up to the third year of life, afterwards dynamics is lower showing around seventh year acceleration of growth termed “preadolescent spurt”. Acceleration is also present during adolescence. After adolescence growth of the column is slowed down considerably being completed together with end of individual’s overall growth.